TA’LIMIY RESURSLAR YARATISHDA WEB-TEXNOLOGIYALARDAN FOYDALANISH - Kadirov, U.E.; Tursunov, S.Q. (SCIENCE and SOCIETY, 2024)
This article discusses the issues of using services based on web technologies: platforms such as Kahoot, Canva, Calameo, MindMeister, PhotoPeach as a means of creating electronic educational resources.
Keywords: web technology; educational resource; infographics; digital technology; multimedia posters; slide show; graphic editors; interactive knowledge card; use; creation